Aerodynamic circulation control for flapless flight control of an unmanned air vehicle - Buonanno, Annalisa (Cranfield University, 2009)
The supporting Flight Dynamics research contribution to the design of Demon, a flapless UAV demonstrator which is the subject of the national research programme FLAVIIR, is described in this thesis. In particular, an integrated flight control and fluidic control system which employs aerodynamic circulation control (CC) to enhance, or replace a conventional aileron is presented. The elimination, or reduction in size, of hinged flight control surfaces on an aircraft offers the possibility of reducing aircraft signature and reducing maintenance requirements; fluidic maneuver effectors provide the opportunity to produce the forces and moments required for flight vehicle maneuvering without using conventional control surfaces. A novel alternative to a conventional single slot trailing edge CC actuator that enables proportional bi-directional control was developed. The CC actuator was manufactured and tested, and experimental evaluation confirmed that bi-directional incremental lift generation comparable to that produced by a mechanical flap of similar trailing edge span is entirely feasible. Wind tunnel tests of a 50% full-span scale Demon model were carried out to establish a representative aerodynamic model of the vehicle. A high fidelity 6DoF simulation of the air vehicle was developed, based on the wind tunnel data and was used to assess vehicle trim, stability and control properties. A mathematical model of the flow control actuator, for interfacing the CC system with the flight control system, was developed and incorporated in the dynamic model of the vehicle. The model determined flapless performance and controllability of the aircraft and, in particular, specific saturation limits and their impact on different phases of flight. Also, the requirements for a secondary air supply system for the CC system and practical values of the volumetric air flow requirement have been assessed. A semi-autonomous primary Flight Control System to enable command and control by a remote pilot throughout the flight was developed. A novel re-configurable control architecture that shares control moment demand between conventional flaps and fluidic motivators was designed and demonstrated to provide a sufficient degree of safety and a flexibility to facilitate future experimental flight research. The results of the research study showed the CC actuator to be a practical solution to the problem of direct flow control at subsonic velocities and, hence, to have significant potential to act as a direct replacement for a flap type control surface. Roll control power equivalent to that of conventional ailerons can be achieved at practical trailing edge slot blowing conditions. Thus, it is concluded that the CC actuator, in combination with conventional elevator and rudder, can effectively control the Demon over its proposed flight envelope.